LINGUISTIC CHARACTERISTICS AND PECULIARITIES OF INTERCULTURAL COMMUNICATION - Hazratkulova, Dilnoza Shukhratovna; Suleymanova, N.M (Educational Research in Universal Sciences, 2022)
Communication classes are conducted in interactive form and involve role playing and training activities, wherei n intercultural communication peculiarities are taken into consideration. This article focuses on the recognition and respect of cultural differences, simple assimilation, and supports the development of intercultural sensitivity on the part of individuals and organizations to enable empathic understanding and competent coordination of action across cultural differences.